2012
DOI: 10.1063/1.4759087
|View full text |Cite
|
Sign up to set email alerts
|

The roles of hydrogen in the diamond/amorphous carbon phase transitions of oxygen ion implanted ultrananocrystalline diamond films at different annealing temperatures

Abstract: We report that the diffusion and desorption of hydrogen (H) play a key role in the diamond/amorphous carbon phase transitions of O+-implanted UNCD films at different annealing temperatures (Ta) by using high resolution transmission electronic microscopy (HRTEM), vis-uv Raman, and Fourier transform infrared (FTIR) spectroscopy measurements. The results of HRTEM and uv Raman spectroscopy measurements show that with Ta increasing from 500 to 900 °C, the amorphous carbon in grain boundaries (GBs) transits to diamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…According to [ 45 ], diamond films prepared mainly by the CVD method consist of many small micro-/nano-crystalline diamonds surrounded by a graphitic or amorphous carbon phase mainly occurring at their grain boundaries. Due to the presence of these phases, C-H bonds and C-C and C=C transpolyacetal chains are bent/stretched, which causes the appearance of a Raman peak in the region of 1140 cm −1 [ 46 , 47 ] (see the NDs pattern in Figure 6 ). Additionally, the authors of [ 45 ] state that the graphitic (G) peak observed in NDs films prepared in this way was shifted from the graphitic peak of 1580 cm −1 downwards to a broad band in the region of 1500 to 1600 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to [ 45 ], diamond films prepared mainly by the CVD method consist of many small micro-/nano-crystalline diamonds surrounded by a graphitic or amorphous carbon phase mainly occurring at their grain boundaries. Due to the presence of these phases, C-H bonds and C-C and C=C transpolyacetal chains are bent/stretched, which causes the appearance of a Raman peak in the region of 1140 cm −1 [ 46 , 47 ] (see the NDs pattern in Figure 6 ). Additionally, the authors of [ 45 ] state that the graphitic (G) peak observed in NDs films prepared in this way was shifted from the graphitic peak of 1580 cm −1 downwards to a broad band in the region of 1500 to 1600 cm −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have revealed a temperature dependence of the preferred location of hydrogen within the structure of UNCD. 26 TPA chains are stable up to 1123 K, with temperatures greater than 1173 K resulting in the shortening of TPA chains and a subsequent decrease of the amount of hydrogen bonded to TPA chains in grain boundaries. During this transition, however, the amount of hydrogen bonded to the surface of diamond grains increases.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Raman spectra were analyzed by fitting a third-order background and five Gaussian peak shape functions to the collected spectra using a routine written in the software package Mathematica . Four of the peaks have previously been assigned to trans -polyactylene (TPA) at the grain boundary (ν 1 and ν 3 ) and carbon ( D and G ) components of the UNCD film. , A fifth peak (ν 2 ) has previously been assigned to TPA (∼1210 cm –1 ) or vibrational density of states contributions from small diamond grains (∼1200 cm –1 ), and is only observed via fitting . The characteristic diamond Raman peak at 1332 cm –1 was not included in the analysis as its contribution is negligible in visible Raman analysis of films grown with minimal hydrogen in the plasma, and it was not discernible in any of the spectra.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations